Who can speak that language? Eleven‐month‐old infants have language‐dependent expectations regarding speaker ethnicity. Issue 6 (22nd April 2019) - May, Lillian; Baron, Andrew S.; Werker, Janet F.
Abstract: Research demonstrates that young infants attend to the indexical characteristics of speakers, including age, gender, and ethnicity, and that the relationship between language and ethnicity is intuitive among older children. However, little research has examined whether infants, within the first year, are sensitive to the co‐occurrences of ethnicity and language. In this paper, we demonstrate that by 11 months of age, infants hold language‐dependent expectations regarding speaker ethnicity. Specifically, 11‐month‐old English‐learning Caucasian infants looked more to Asian versus Caucasian faces when hearing Cantonese versus English (Studies 1 and 3), but did not look more to Asian versus Caucasian faces when paired with Spanish (Study 2), making it unlikely that they held a general expectation that unfamiliar languages pair with unfamiliar faces. Moreover, infants who had regular exposure to one or more significant non‐Caucasian individuals showed this pattern more strongly (Study 3). Given that infants tested were raised in a multilingual metropolitan area—which includes a Caucasian population speaking many languages, but seldom Cantonese, as well as a sizeable Asian population speaking both Cantonese and English—these results are most parsimoniously explained by infants having learned specific language–ethnicity associations based on those individuals they encountered in their environment.